Analysis of Local Culinary Potential in Supporting the Tourism Industry in Gunungsari West Lombok - Nurul Farikhatir Rizkiyah; M. Ilham Faridi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The study aims to analyze: 1) local culinary potential (2) supporting factors; and (3) factors inhibiting the potential of local culinary in supporting the Tourism Industry. This research is qualitative research. The sampling technique was purposive sampling. Data collection techniques used are observation, interviews and documentation. The results showed that: (1) local culinary served in daily life as a staple food or the habit of consuming the dish. There are 6 types of local culinary classifications in the form of rice, vegetables, side dishes, satay, traditional snacks, and crackers or chips; (2) supporting factors, namely local cuisine must be maintained and developed so that it can provide additional income for villagers and be able to preserve local values, especially in the food they have; and (3) inhibiting factors, namely the lack of training for human resources in the form of training on sanitation and hygiene in food processing, culinary product packaging and lack of promotion of culinary products.